Deexcitation Probabilities of Ne(3P2) by Xe for the Case E << D - Khadka, Deba Bahadur (Journal of Nepal Chemical Society, 2010)
The deexcitaion probability calculation of the total Penning ionization cross section for Ne(3P2) by Xe has been made in the region of the collisional energy from 18.5 to 38.1 meV. The experimental cross sections have been compared with the deexcitation probability for Ne(3P2) by Xe. Considering the magnitude of the mean collisional energy with respect to D, the application of the analysis in the case E >> D is expected to be more appropriate than in the case E << D. For further insight into this results, it is also of great importance to evaluate theoretical investigations of Ne(3P2) by Xe for the case E >> D. Keywords: Metastable atoms, deexcitation probabilities, pulse radiolysis, collisional energy, potential well depth DOI: 10.3126/jncs.v25i0.3304 Journal of Nepal Chemical Society Volume 25, 2010 pp 70-74